Predictors of Long-Term Pain After Hip Arthroplasty in Patients With Femoral Neck Fractures: A Cohort Study. (November 2020) - Noori, Atefeh; Sprague, Sheila; Bzovsky, Sofia; Schemitsch, Emil H.; Poolman, Rudolf W.; Frihagen, Frede; Axelrod, Daniel; Heels-Ansdell, Diane; Bhandari, Mohit; Busse, Jason W.
Abstract : Objectives: To identify factors associated with the development of prolonged pain after hip fracture surgery. Design: Secondary analysis of a randomized controlled trial. Setting: Eighty hospitals in 10 countries. Patients/Participants: One thousand four hundred forty-one hip fracture patients in the HEALTH trial. Interventions: Total hip arthroplasty or hemiarthroplasty. Main Outcome Measures: Moderate-to-severe pain (at least 2 activities on the Western Ontario and McMaster Universities Osteoarthritis questionnaire pain subscale with scores ≥2) at 12 and 24 months after hip arthroplasty. Results: Of 840 and 726 patients with complete baseline data and outcomes at 1-year and 2-year follow-up, 96 (11.4%) and 80 (11.0%) reported moderate-to-severe pain, respectively. An increased risk of pain at both 1 and 2 years after surgery was associated with reporting moderate-to-severe hip pain before fracture [absolute risk increase (ARI) 15.3%, 95% confidence interval (CI) 6.44%–24.35%; ARI 12.5%, 95% CI 2.85%–22.12%, respectively] and prefracture opioid use (ARI 15.6%, 95% CI 5.41%–25.89%; ARI 21.1%; 95% CI 8.23%–34.02%, respectively). Female sex was associated with an increased risk of persistent pain at 1 year (ARI 6.2%, 95% CI 3.53%–8.84%). A greater risk of persistent pain at 2 years was associated with younger age (⩽79-year-old; ARI 6.3%; 95% CI 2.67%–9.91%) and higher prefacture functional status (ARI 10.7%; 95% CI 3.80%–17.64%). Conclusions: Among hip fracture patients undergoing arthroplasty, approximately one in 10 will experience moderate-to-severe pain up to 2 years after surgery. Younger age, female sex, higher functioning prefracture, living with hip pain prefracture, and use of prescription opioids were predictive of persistent pain. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.